Broadway North: craft in Canadian creative industry production. (1st April 2016) - ,
Abstract : This article considers how the autonomy and occupational identities of craft workers are shaped by the organisation of production in culture industry workshops that fabricate theatrical display environments. Representation of craft autonomy in the literature on creative labour is sparse and tends to overlook the fact that craft autonomy is different in some respects from artistic autonomy. Drawing on qualitative semi-structured interviews with craft workers, designers and culture industry workshop owners and managers, this study examines the digitalisation and industrialisation of theatre production work. The article contributes to an understanding of craft autonomy as collective, part of a community of practice in a context in which experiential and practice-based knowledge is mediated by digital fabrication tools and the structural conditions of the work.